RICE FIELD DISCHARGE MODELLING BY TAKING INTO ACCOUNT THE CONTRIBUTION OF PREVIOUS TERRACE DRAINAGE - IRIANTO, GATOT; LAS, IRSAL (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2000)
Its been a long time that paddy terraces have been used in order to modify local hydraulic characteristics, aiming thus at a better evenness in water collecting and distribution. Nevertheless, the quantification of water transfer mechanism in terraces has still to be fully understood. Research on modeling for water transfer has been carried out to answer this issue.The two following reservoir linear laws have been used to represent water transfer in the terrace: (1) taking into account continuous discharge contribution of the precedent terrace and (2) taking into account discontinuous discharge contribution of the precedent terrace. The results of research show that a universal discharge equation for the nth terrace, based on the reservoir linear law derived through inductive method, can be described as:where : Qn is the discharge from the nth terrace (m3/s), Q0 the initial discharge (m3/s), k is a reservoir constant (s-1),and t is the time(s). According to the physical law, the inflow drained from the previous terrace has to be taken into account, but in this case,discharge modeling is reduced to the time when linear reservoir law still applies. This is because time taken for the terrace to be fully drained-dry would be infinite: thus when the water level is under the drain level axis, the linear reservoir law does not apply anymore. At this time, the main part of the stock can not be computed using surface and water level, because of local surface roughness. To find a solution, the debit was modeled byassuming that water on the terrace was fully drained when the water surface reaches exactly half the diameter of the drain pipe. Results of such a model show that the debit thus evaluated approach the debit measured with a coefficient F (criterion of Nash and Sutcliffe) variegating between 0.97 and 0.98. With such results this model can be accepted, assumingas a basic hypothesis that the terrace is dry when water its surface reaches half of the drain pipe diameter.